Lithium secondary battery positive electrode active material precursor, positive electrode active material comprising same, and method for preparing positive electrode active material
By using a concentration gradient lithium transition metal oxide with transition metal component as the precursor of the positive electrode active material, the problems of degradation in performance of lithium secondary batteries at high temperatures and expensive cobalt are solved, and the preparation of a positive electrode active material with improved stability and lifetime characteristics is achieved.
Patent Information
- Application Number
- CN202380059882.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-16
- Filing Date
- 2023-08-16
- Publication Date
- 2025-04-01
AI Technical Summary
The performance of the positive electrode active materials of existing lithium secondary batteries decreases at high temperatures, and cobalt is expensive, which affects the widespread application of power sources such as electric vehicles.
A concentration gradient lithium transition metal oxide with transition metal component is used as the precursor of the positive electrode active material. By controlling the XRD peak ratio and calcining conditions, a positive electrode active material with improved stability and lifetime characteristics was prepared.
It effectively reduces internal cracks of particles, improves the stability and life of the material, reduces processing costs, and limits the residual Li2CO3 content, improving high-temperature characteristics.
Smart Images

Figure CN119744249A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a secondary battery, and more particularly to a precursor of a positive electrode active material for a lithium secondary battery, a lithium secondary battery positive electrode active material containing the precursor, and a preparation method thereof. Background Art
[0002] Lithium secondary batteries generally consist of a positive electrode containing a positive active material, a negative electrode containing a negative active material, a separator, and an electrolyte. They are charged and discharged through the intercalation and deintercalation of lithium ions. These batteries offer advantages such as high energy density, high electromotive force, and high capacity, and are therefore used in a variety of fields.
[0003] In addition, in lithium secondary batteries, improving high temperature performance such as high temperature storage characteristics and high temperature cycle characteristics is an important issue that needs to be addressed. For example, after the positive electrode active material is coated on the collector and pressed, if the internal total pore volume is high, there is a problem that the high temperature performance of the positive electrode is likely to decrease. Therefore, it is necessary to minimize the changes in the electrode structure and the changes in the internal total pore volume generated during electrode pressing, thereby improving high temperature characteristics when developing positive electrode materials for lithium secondary batteries such as secondary batteries for fast charging.
[0004] In addition, with the technological development and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among secondary batteries, lithium secondary batteries with high energy density and working potential, long cycle life and low self-discharge rate have been commercialized and widely used.
[0005] In addition, with the increasing concern about environmental issues, people are increasingly interested in electric vehicles and hybrid electric vehicles because they can replace fossil fuel-using vehicles such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution, and the use of lithium secondary batteries as a power source for electric vehicles and hybrid electric vehicles is being actively studied.
[0006] With technological advancements and the growing demand for electric vehicles, the demand for lithium secondary batteries (Li-Nickel-Cobalt-Manganese) as a large-scale battery energy source is rapidly increasing. Interest in lithium-nickel-cobalt-manganese composite oxides (Li-Nickel-Cobalt-Manganese) composite oxides as cathode active materials for Li-Nickel-Cobalt-Manganese composite oxides is also rapidly increasing. Among these composite oxides, cobalt plays a particularly important role in providing cathode active materials with high operating voltages and excellent efficiency characteristics.
[0007] However, since cobalt is expensive, its large-scale use in power sources such as electric vehicles is limited. Recently, the price of cobalt has soared and the content of cobalt has gradually decreased, so a solution that can compensate for stability and lifespan is needed.
[0008] Another approach to improving the stability of positive electrode active materials has been proposed, using lithium transition metal oxides with a concentration gradient, where the concentration of the transition metal component gradually changes from the surface to the interior of the positive electrode active material. However, lithium transition metal oxides with a concentration gradient cannot fully control the internal cracks that develop within the particles during charge and discharge. Furthermore, the complex process used to achieve this leads to high processing costs and difficulty in controlling quality. Furthermore, lithium transition metal oxides with a concentration gradient cannot fully control the internal cracks that develop within the particles during charge and discharge. Summary of the Invention
[0009] Technical problems to be solved
[0010] In the processing of positive electrode active materials, a positive electrode active material precursor can be provided, which has low processing cost and easy quality control. By controlling the internal cracks of the particles generated during the charge and discharge process, a positive electrode active material with improved stability and life characteristics can be prepared.
[0011] A positive electrode active material including the positive electrode active material precursor having the aforementioned advantages can be provided.
[0012] A method for preparing a positive electrode active material having the aforementioned advantages may be provided.
[0013] Technical Solution
[0014] According to the positive electrode active material precursor of one embodiment of the present invention, wherein, for the XRD peak, I 001 / I 100 The ratio is 0.5 to 6, I 001 / I 101 The ratio is 0.6 to 3, I 001 / I 102 The ratio is 2.5 to 8. 001 / I 110 The ratio is 1.5 to 11. 001 / I 111 The ratio is 2 to 14, I 100 / I 001 The ratio is 0.1 to 3.1, I 100 / I 101 The ratio is 0.1 to 1.5, I 100 / I 102 The ratio is 1.0 to 7.3, I 100 / I 110 The ratio is 1.5 to 3.2, and I 100 / I 111 The ratio is at least any one of 2.5 to 5.3.
[0015] In one embodiment, the positive electrode active material precursor can satisfy at least one of the following conditions: the half-width of the diffraction peak on the (001) plane is in the range of 0.1 to 3.0, the half-width of the diffraction peak on the (100) plane is in the range of 0.1 to 2.8, the half-width of the diffraction peak on the (101) plane is in the range of 0.36 to 1.0, the half-width of the diffraction peak on the (102) plane is in the range of 0.1 to 2.0, and the half-width of the diffraction peak on the (110) plane is in the range of 0.1 to 3.0.
[0016] In one embodiment, the positive electrode active material precursor may have a structure in which at least one transition metal layer and an oxygen layer are stacked.
[0017] In another embodiment, the positive active material precursor is composed of at least one primary particle, and the c-axis crystal constant value of the primary particle may be 300 nm to 700 nm.
[0018] A positive electrode active material according to another embodiment of the present invention comprises <001> At least one positive electrode active material precursor having hydrogen bonds in a direction, the positive electrode active material may be a single particle, and the single particle contains 500 to 2000 ppm of Li2CO3 in terms of weight%.
[0019] In one embodiment, the positive electrode active material includes LiOH, and the LiOH and the Li2CO3 may satisfy the following Formula 1.
[0020] <Formula 1>
[0021] 0.5≤[LiOH] / [Li2CO3]≤1.9
[0022] In Formula 1, [LiOH] represents the content of LiOH, and [Li2CO3] represents the content of Li2CO3.
[0023] In one embodiment, the LiOH may include 1000 to 4000 ppm in terms of weight %.
[0024] In one embodiment, the average particle size (D50) of the positive active material may be 2 to 20 μm.
[0025] In one embodiment, the specific surface area may be from 1 to 30 m 2 / g.
[0026] In one embodiment, the positive electrode active material may be a lithium nickel composite oxide represented by the following Chemical Formula 1.
[0027] <Chemical Formula 1>
[0028] Li x [Ni y Co z Mnw M v ]O2
[0029] In the above chemical formula 1, M is one or more selected from Ba, Ca, Zr, Ti, Mg, Ta, Nb and Mo, 0.9 <x<1.2,0.8<y<1,0<z<0.8,0<w<0.05,0≤v≤0.2。
[0030] According to another embodiment of the present invention, a method for preparing a positive electrode active material includes: adding an aqueous solution containing a sodium or potassium-based substance to form initial reaction conditions in a reactor; adding an aqueous solution containing at least one of nickel, cobalt, and manganese salts, a complex ion former, and a pH adjuster to the reactor to prepare a reaction solution; filtering the reaction solution to prepare a metal composite hydroxide; mixing the metal composite hydroxide and a lithium raw material to prepare a positive electrode active material precursor; and calcining the positive electrode active material precursor. The aqueous solution containing the sodium or potassium-based substance may contain 5 to 10 parts by weight of the sodium or potassium-based substance relative to 100 parts by weight of water.
[0031] In one embodiment, the sodium or potassium-based substance may include at least any one of sodium sulfate, sodium hydrochloride, potassium hydrochloride, and potassium sulfate.
[0032] In one embodiment, in the step of adding an aqueous solution of a metal salt containing at least one of nickel, cobalt, and manganese, a complex ion former, and a pH adjuster into the reactor, the ratio of the flow rate of aqueous ammonia to the flow rate of the aqueous solution of the metal salt may be 0.06 to 0.3.
[0033] In one embodiment, the flow rate of the aqueous metal salt solution may be 2.5 to 3.5 L / hour.
[0034] In one embodiment, the calcining step may be performed at 750 to 1100°C.
[0035] In one embodiment, the calcining step may be performed for 5 to 30 hours.
[0036] In one embodiment, in the step of adding an aqueous solution of a metal salt containing at least one of nickel, cobalt, and manganese, a complex ion former, and a pH adjuster into the reactor, the pH in the reactor may be adjusted to 10 to 12.
[0037] Beneficial effects
[0038] According to one embodiment of the present invention, the positive electrode active material precursor is <001> direction to form hydrogen bonds and grow.
[0039] According to another embodiment of the positive active material of the present invention, which includes a precursor having the aforementioned advantages to form a single particle, cracks generated at polycrystalline boundaries are reduced, thereby improving stability and life characteristics, and the content of residual Li2CO3 is limited to a predetermined range.
[0040] According to a method for preparing a positive electrode active material according to yet another embodiment of the present invention, a positive electrode active material having the aforementioned advantages is prepared by controlling the content of the complex ion former. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figures 1a to 1c SEM photographs of positive electrode active material precursors according to examples of the present invention and comparative examples are shown.
[0042] Figure 2 XRD peak intensity values of Examples according to the present invention and Comparative Examples are shown.
[0043] Figures 3a to 3c SEM photographs of positive electrode active materials of lithium secondary batteries according to examples of the present invention and comparative examples are shown.
[0044] Figure 3a and Figure 3b Graphs showing capacity characteristics and lifespan characteristics of positive electrode active materials for lithium secondary batteries according to examples of the present invention and comparative examples.
[0045] Figure 4a and Figure 4b Graphs showing capacity characteristics and lifespan characteristics of positive electrode active materials for lithium secondary batteries according to examples of the present invention and comparative examples.
[0046] Figure 5 An SEM photograph of an active material precursor for a lithium secondary battery prepared by adding ammonium sulfate in a comparative example of the present invention is shown. DETAILED DESCRIPTION
[0047] The terms "first," "second," and "third" are used to describe various parts, components, regions, layers, and / or segments, but these parts, components, regions, layers, and / or segments should not be limited by these terms. These terms are only used to distinguish one part, component, region, layer, and / or segment from another part, component, region, layer, and / or segment. Therefore, a first part, component, region, layer, and / or segment described below could also be described as a second part, component, region, layer, and / or segment without departing from the scope of the present invention.
[0048] The terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the present invention. Unless the context clearly indicates otherwise, the singular form used is intended to include the plural form. It should also be understood that the term "comprising" as used in this specification may specifically refer to a certain characteristic, field, integer, step, action, element and / or component, but does not exclude the presence or addition of other characteristics, fields, integers, steps, actions, elements and / or components.
[0049] If a part is described as being "on" another part, then the other part may be directly on the other part or there may be another part therebetween. If a part is described as being "directly on" another part, then no other part may be therebetween.
[0050] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Dictionary-defined terms should be interpreted as having the same meaning as that in the relevant technical literature and disclosed herein, and should not be interpreted in an idealized or overly formal sense.
[0051] Hereinafter, embodiments of the present invention will be described in detail. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments. The present invention is subject to the scope of the claims.
[0052] According to an embodiment of the present invention, the positive active material precursor of the lithium secondary battery, wherein the XRD peak value can satisfy I 001 / I 100 The ratio is 0.5 to 6, I 001 / I 101 The ratio is 0.6 to 3, I 001 / I 102 The ratio is 2.5 to 8. 001 / I 110 The ratio is 1.5 to 11. 001 / I 111 The ratio is 2 to 14, I 100 / I 001 The ratio is 0.1 to 3.1, I 100 / I 101 The ratio is 0.1 to 1.5, I 100 / I 102 The ratio is 1.0 to 7.3, I 100 / I 110 The ratio is 1.5 to 3.2, and I 100 / I 111 The ratio is at least any one of 2.5 to 5.3. Specifically, for the XRD peak, I 001It can be a peak value that satisfies the range of 18.5±1.0°. More specifically, the I 001 It can represent a C-axis growth precursor that grows by forming hydrogen bonds.
[0053] For XRD peaks, I 100 It can be a peak that satisfies the range of 33.0±1.0°. For XRD peak, I 101 The peak satisfies the range of 38.5±1.5° and can represent the peak of the A-axis growth precursor.
[0054] For XRD peaks, I 102 It can be a peak that satisfies the range of 52.5±1.5°. For XRD peak, I 110 It can be a peak value that meets the range of 59±1.5°, I 111 It may be a peak value that satisfies the range of 63±1.0°.
[0055] I 001 / I 100 The ratio is one of the indicators for judging whether the precursor grows by forming hydrogen bonds in the 001 direction. The higher the ratio, the more likely the precursor grows by forming hydrogen bonds in the 001 direction. 001 / I 100 The ratio may be 0.5 to 6. Specifically, the I 001 / I 100 The ratio may be 2 to 6. Specifically, the I 001 / I 100 The ratio can be from 2.3 to 4.4.
[0056] Because of the I 001 / I 100 The ratio falling within the aforementioned range has the advantage of enabling single-particle positive electrode active material to be obtained by calcining the precursor. If the ratio exceeds the upper limit, capacity issues may arise when used in batteries, while if the ratio exceeds the lower limit, single-particle formation of the positive electrode active material may be difficult.
[0057] I 001 / I 101 The ratio is one of the indicators for judging whether the precursor grows by forming hydrogen bonds in the 001 direction. The higher the ratio, the more likely the precursor grows by forming hydrogen bonds in the 001 direction. 001 / I 101 The ratio may be 0.6 to 3. Specifically, the I 001 / I 101 The ratio may be 1.5 to 3. More specifically, the I 001 / I 101 The ratio may be 1.5 to 1.8.
[0058] Since the I 001 / I 101 When the ratio is within the aforementioned range, cracking at polycrystalline boundaries is reduced, thereby improving stability and lifespan characteristics, and having the advantage of limiting the residual Li2CO3 content. If the ratio exceeds the upper limit, battery application may have capacity issues, while if the ratio exceeds the lower limit, the primary particles become thinner, resulting in an increase in crystal plane boundaries and increased cracking.
[0059] I 001 / I 102 The ratio is one of the indicators for judging whether the precursor grows by forming hydrogen bonds in the 001 direction. The higher the ratio, the more likely the precursor grows by forming hydrogen bonds in the 001 direction. 001 / I 102 The ratio may be 2.5 to 8. Specifically, the I 001 / I 102 The ratio can be from 4.9 to 6.7.
[0060] Because of the I 001 / I 102 The ratio falling within the aforementioned range has the advantage of enabling single-particle positive electrode active material to be obtained by calcining the precursor. If the ratio exceeds the upper limit, capacity issues may arise when used in batteries, while if the ratio exceeds the lower limit, single-particle formation of the positive electrode active material may be difficult.
[0061] I 001 / I 110 The ratio is one of the indicators for judging whether the precursor grows by forming hydrogen bonds in the 001 direction. The higher the ratio, the more likely the precursor grows by forming hydrogen bonds in the 001 direction. 001 / I 110 The ratio may be 1.5 to 11. Specifically, the I 001 / I 110 The ratio may be 4.0 to 10.5. More specifically, the I 001 / I 110 The ratio can be from 4.2 to 10.3.
[0062] Because of the I 001 / I 110 The ratio falling within the aforementioned range has the advantage of enabling single-particle positive electrode active material to be obtained by calcining the precursor. If the ratio exceeds the upper limit, capacity issues may arise when used in batteries, while if the ratio exceeds the lower limit, single-particle formation of the positive electrode active material may be difficult.
[0063] I 001 / I111 The ratio is one of the indicators for judging whether the precursor grows by forming hydrogen bonds in the 001 direction. The higher the ratio, the more likely the precursor grows by forming hydrogen bonds in the 001 direction. 001 / I 111 The ratio may be 2 to 14. Specifically, the I 001 / I 111 The ratio may be 7.0 to 13.5. More specifically, the I 001 / I 111 The ratio can be from 7.4 to 13.0.
[0064] Because of the I 001 / I 111 The ratio falling within the aforementioned range has the advantage of enabling single-particle positive electrode active material to be obtained by calcining the precursor. If the ratio exceeds the upper limit, capacity issues may arise when used in batteries, while if the ratio exceeds the lower limit, single-particle formation of the positive electrode active material may be difficult.
[0065] In one embodiment, I 100 / I 001 The ratio can be between 0.1 and 3.1. 100 / I 001 The ratio can be between 0.23 and 0.44. 100 / I 101 The ratio may be between 0.1 and 1.5. 100 / I 101 The ratio can satisfy 0.34 to 0.78.
[0066] In one embodiment, I 100 / I 102 The ratio may be between 1.0 and 7.3. 100 / I 102 The ratio may be between 1.13 and 2.95. 100 / I 110 The ratio can be between 1.5 and 3.2. 100 / I 110 The ratio may be between 1.83 and 2.37. 100 / I 111 The ratio can be between 2.5 and 5.3. 100 / I 111 The ratio can be between 2.98 and 3.28. 100 / I 001 Ratio, I 100 / I 101 Ratio, I 100 / I102 Ratio, I 100 / I 110 Ratio or I 100 / I 111 When the ratio falls within the above range, it is advantageous in that single particles can be easily obtained when preparing the positive electrode active material.
[0067] In one embodiment, the positive electrode active material precursor can satisfy at least one of the following conditions: the diffraction peak half-maximum width (FWHM) on the (001) plane is in the range of 0.1 to 3.0, the diffraction peak half-maximum width on the (100) plane is in the range of 0.1 to 2.8, the diffraction peak half-maximum width on the (101) plane is in the range of 0.36 to 1.0, the diffraction peak half-maximum width on the (102) plane is in the range of 0.1 to 2.0, and the diffraction peak half-maximum width on the (110) plane is in the range of 0.1 to 3.0.
[0068] For the Full Width At Half Maximum (FWHM), specifically, it can satisfy at least one of the following ranges: the half-maximum width of the diffraction peak on the (001) plane is in the range of 0.27 to 0.42, the half-maximum width of the diffraction peak on the (100) plane is in the range of 0.21 to 0.34, the half-maximum width of the diffraction peak on the (101) plane is in the range of 0.37 to 0.55, the half-maximum width of the diffraction peak on the (102) plane is in the range of 0.56 to 1.03, and the half-maximum width of the diffraction peak on the (110) plane is in the range of 0.33 to 0.66.
[0069] In one embodiment, the positive electrode active material precursor may have a structure comprising at least one transition metal layer and an oxygen layer stacked together. The transition metal layer may be composed of nickel, cobalt, manganese, or a mixture thereof. The transition metal layer may form a dense aggregate through the stacking of the oxygen layer and hydrogen bonding. This dense aggregate facilitates the formation of single particles during the calcination process in the preparation of the positive electrode active material described below.
[0070] In one embodiment, the positive electrode active material precursor includes at least one primary particle, and the primary particle may have a c-axis value of 300 nm to 700 nm. Specifically, with the dissolution of the transition metal layer and the reduction of the electrostatic repulsion of the (001) plane, the primary particles constituting the positive electrode active material precursor will form thicker and larger. Therefore, when synthesizing the positive electrode active material, a single particle can also be synthesized at a lower temperature.
[0071] In one embodiment, the span value ((D90-D10) / D50) of the ratio of the difference between the D90 particle size and the D10 particle size of the positive electrode active material precursor may be within a range of 0.55 to 0.75. Specifically, the span value may be within a range of 0.55 to 0.70, and more specifically, within a range of 0.61 to 0.67.
[0072] The D10, D50, and D90 particle sizes refer to the particle sizes when the volume ratio of precursor particles with different particle sizes reaches 10%, 50%, and 90%, respectively. If the span value range exceeds the upper limit, the fine powder will increase the overall specific surface area when used in batteries, resulting in reduced initial charge and discharge efficiency. If the span value range exceeds the lower limit, the industrial processing of powders with very small particle size deviations will significantly reduce production yield and increase costs.
[0073] In another embodiment of the present invention, the positive electrode active material of the lithium secondary battery can be <001> The cathode active material precursor is formed by calcining at least one cathode active material precursor having hydrogen bonds in the direction. As for the detailed description of the cathode active material precursor, reference can be made to the above content within the scope of no contradiction.
[0074] In one embodiment, the lithium secondary battery positive electrode active material can be a single particle, and the single particle contains 500 to 2000 ppm of Li2CO3 by weight. Specifically, the content of the Li2CO3 can be 800 to 1800 ppm. Since the Li2CO3 is included within the aforementioned range, there is an advantage of reducing residual lithium. If the range of the Li2CO3 exceeds the upper limit, there are problems such as deterioration of life characteristics and increased instability.
[0075] The single particle refers to a positive electrode active material with no distinction between primary particles and secondary particles. The primary particles are primary structures formed by the entire primary particle being crystallized into a single particle, while the secondary particles are aggregates formed by physical or chemical bonding between multiple primary particles. The single particle shape of the positive electrode active material for lithium secondary batteries reduces cracking at polycrystalline boundaries, resulting in a positive electrode active material with excellent stability and lifespan.
[0076] In one embodiment, the positive active material of the lithium secondary battery includes LiOH and may satisfy the following Formula 1.
[0077] <Formula 1>
[0078] 0.5≤[LiOH] / [Li2CO3]≤1.9
[0079] In Formula 1, [LiOH] represents the content of LiOH, and [Li2CO3] represents the content of Li2CO3.
[0080] The formula 1 may satisfy a range of 0.5 to 1.9. Specifically, the formula 1 may satisfy a range of 1.1 to 1.75.
[0081] Since the content ratio of lithium hydroxide (LiOH) to lithium carbonate (Li2CO3) satisfies the aforementioned range, it has the advantages of reducing the resistance of the active material and improving stability and life characteristics. If the range of Formula 1 exceeds the upper limit of the range, instability increases and there is a problem of deterioration of life characteristics.
[0082] In one embodiment, the LiOH content may be 1000 to 4000 ppm by weight. Specifically, the LiOH content may be 1400 to 2000 ppm by weight. Including the LiOH content within the aforementioned range has the advantage of limiting residual LiOH and reducing gas generation. If the LiOH content exceeds the upper limit, there is a problem of increased gas generation and increased instability.
[0083] In one embodiment, the average particle size (D50) of the lithium secondary battery positive electrode active material may be 2.0 to 20 μm. Specifically, the average particle size (D50) may be 3.6 to 4.4 μm. More specifically, the average particle size (D50) may be 3.80 to 4.06 μm.
[0084] If the average particle size (D50) exceeds the upper limit, there is a problem of increased total internal pores after rolling. If the average particle size (D50) exceeds the lower limit, there is a problem of stability.
[0085] In one embodiment, the specific surface area of the positive electrode active material of the lithium secondary battery may be 1 to 30 m 2 / g. Specifically, the specific surface area can be 5 to 10m 2 / g.
[0086] If the specific surface area exceeds the upper limit of the range, a large number of gaps may be generated between the secondary particles formed by the aggregation of the primary particles. If the specific surface area exceeds the lower limit of the range, the secondary particles formed by the aggregation of the primary particles may be too dense.
[0087] In one embodiment, the positive active material of the lithium secondary battery may be a lithium nickel composite oxide satisfying the following Chemical Formula 1.
[0088] <Chemical Formula 1>
[0089] Li x[Ni y Co z Mn w M v ]O2
[0090] In the above chemical formula 1, M is one or more selected from Ba, Ca, Zr, Ti, Mg, Ta, Nb and Mo, 0.9 <x<1.2,0.8<y<1,0<z<0.8,0<w<0.05,0≤v≤0.2。
[0091] According to another embodiment of the present invention, a method for preparing a positive electrode active material includes: a step of adding an aqueous solution containing a sodium or potassium-based substance to form initial reaction conditions in a reactor; a step of adding an aqueous solution containing at least one of nickel, cobalt, and manganese salts, a complex ion former, and a pH adjuster to the reactor; a step of filtering the reaction solution to prepare a metal composite hydroxide; a step of mixing the metal composite hydroxide and a lithium raw material to prepare a positive electrode active material precursor; and a step of calcining the positive electrode active material precursor.
[0092] In the step of adding an aqueous solution containing a sodium- or potassium-based substance to form an initial reaction condition in the reactor, the sodium- or potassium-based substance may include at least one of sodium sulfate (Na2SO4), sodium hydrochloride (NaClO3), potassium sulfate (K2SO4), and potassium hydrochloride (KClO3). For example, the sodium-based substance may be sodium sulfate (Na2SO4).
[0093] In one embodiment, the aqueous solution containing the sodium- or potassium-based substance may contain 5 to 10 parts by weight of the sodium- or potassium-based substance relative to 100 parts by weight of water. Inclusion of the sodium- or potassium-based substance within the aforementioned range provides the advantage of thickening the primary particles. If the upper limit of the range is exceeded, the thickness of the primary particles may increase significantly. If the lower limit of the range is exceeded, the thickness of the primary particles may decrease significantly.
[0094] By forming the initial reaction conditions in the reactor using the sodium or potassium-based substance, it can be confirmed that the primary particles tend to be thicker and larger when preparing the positive electrode active material precursor. For the positive electrode active material prepared by the sodium or potassium-based aqueous solution, it can be confirmed that the crystallization of the material using sodium sulfate is more uniform and presents a single crystal form.
[0095] In the step of adding an aqueous metal salt solution containing at least one of nickel, cobalt, and manganese, a complex ion former, and a pH adjuster into the reactor to prepare a reaction solution, the aqueous metal salt solution, the complex ion former, and the pH adjuster can be added in the aforementioned order at predetermined intervals or added simultaneously.
[0096] In the step of adding a metal salt aqueous solution containing at least one of nickel, cobalt, and manganese, a complex ion former, and a pH adjuster into the reactor, the metal salt aqueous solution may be a substance containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, wherein the substance contains at least any one of nickel, cobalt, and manganese. As a non-limiting example, the metal salt aqueous solution containing nickel may be Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O4·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, a fatty acid nickel salt, a nickel halide, or a combination thereof.
[0097] As a non-limiting example, the aqueous metal salt solution containing cobalt may be Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or a combination thereof. As a non-limiting example, the aqueous metal salt solution containing manganese may be Mn2O3, MnO2, Mn3O4, MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate salt, manganese citrate, fatty acid manganese salt, manganese oxyhydroxide, manganese chloride, or a combination thereof.
[0098] In the step of adding an aqueous solution of a metal salt containing at least one of nickel, cobalt and manganese, a complex ion former and a pH adjuster into the reactor to prepare a reaction solution, the complex ion former can form a complex with at least one ion of nickel, cobalt and manganese.
[0099] In one embodiment, in the step of adding an aqueous solution of a metal salt containing at least one of nickel, cobalt, and manganese, a complex ion forming agent, and a pH adjuster to the reactor to prepare a reaction solution, the flow rate of the ammonia solution may be 0.06 to 0.3 relative to the flow rate of the aqueous metal solution. Specifically, the flow rate of the ammonia solution may be 0.1 to 0.2 relative to the flow rate of the aqueous metal solution.
[0100] Since the flow rate of the aqueous metal solution satisfies the above range, a single particle-shaped positive electrode active material can be prepared. If the flow rate exceeds the above range, a single particle-shaped positive electrode active material cannot be prepared.
[0101] In one embodiment, in the step of adding an aqueous solution of a metal salt containing at least one of nickel, cobalt, and manganese, a complex ion former, and a pH adjuster into the reactor to prepare a reaction solution, the pH in the reactor can be adjusted to 10 to 12, specifically 10.5 to 11.5.
[0102] In one embodiment, the calcination step of calcining the positive electrode active material precursor may be performed at 750 to 1100° C. Specifically, the calcination step may be performed at 800 to 1000° C., more specifically, at 780 to 950° C. Due to the calcination step within this temperature range, the primary particles grow thicker and nuclear agglomeration does not occur, thereby having the advantage of being able to prepare a positive electrode active material having a single particle shape.
[0103] In one embodiment, the calcination step of calcining the positive electrode active material precursor may be performed for 5 to 30 hours, specifically, for 8 to 12 hours.
[0104] A lithium secondary battery according to another embodiment of the present invention includes a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode includes the positive electrode active material.
[0105] The positive electrode includes a current collector and a positive electrode active material layer located on the current collector. The positive electrode active material layer includes a positive electrode active material, which may include a lithium secondary battery positive electrode active material according to one of the aforementioned embodiments. The positive electrode active material layer may contain 90% to 99% by weight of the positive electrode active material relative to the total weight of the positive electrode active material layer.
[0106] The positive electrode active material layer further comprises a binder and / or a conductive material. In this case, the binder and the conductive material may each be present in an amount of 1 wt % to 5 wt % relative to the total weight of the positive electrode active material layer.
[0107] The binder serves to effectively bond the positive electrode active material particles to each other and to effectively bond the positive electrode active material to the current collector. Typical examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, and nylon.
[0108] The conductive material is used to impart conductivity to the electrode. Any conductive material can be used as long as it does not cause chemical changes in the resulting battery. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and carbon fibers; metal-based materials such as copper, nickel, aluminum, and silver metal powders or fibers; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0109] As the positive electrode current collector, aluminum foil, nickel foil, or a combination thereof may be used, but is not limited thereto.
[0110] The negative electrode includes a current collector and a negative electrode active material layer formed on the current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0111] The negative electrode active material includes a substance capable of reversibly intercalating and deintercalating lithium ions, lithium metal, a lithium metal alloy, a substance capable of doping and dedoping lithium, or a transition metal oxide.
[0112] As the substance capable of reversibly intercalating and deintercalating lithium ions, any carbon-based negative electrode active material generally used as a carbon material in lithium ion secondary batteries can be used, and typical examples thereof include crystalline carbon, amorphous carbon, or a combination thereof.
[0113] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn can be used.
[0114] Examples of the substance capable of lithium doping and dedoping include Si, SiO x (0<x<2), Si-Y alloy (the Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, but not Si), Sn, SnO2, Sn-Y (the Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, but not Sn), etc.
[0115] Examples of the transition metal oxide include vanadium oxide, lithium vanadium oxide, etc. The negative electrode active material layer also includes a binder and may optionally further include a conductive material.
[0116] The binder plays a role in allowing negative electrode active material particles to be well bonded to each other and allowing the negative electrode active material to be well bonded to the current collector.
[0117] The conductive material is used to impart conductivity to the electrode, and any conductive material can be used as long as it does not cause chemical changes in the constituted battery.
[0118] As the current collector, a material selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer material coated with a conductive metal, and a combination thereof may be used.
[0119] For the negative and positive electrodes, an active material, a conductive material, and a binder are mixed in a solvent to form an active material composition, which is then coated onto a current collector. Such electrode preparation methods are well known in the art and are therefore omitted from this specification. The solvent may be, but is not limited to, N-methylpyrrolidone.
[0120] The electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0121] The non-aqueous organic solvent functions as a medium through which ions participating in the electrochemical reaction of the battery can migrate.
[0122] The lithium salt is a substance that dissolves in an organic solvent and acts as a lithium ion source in the battery to ensure the basic operation of the lithium secondary battery and promote the migration of lithium ions between the positive electrode and the negative electrode.
[0123] Depending on the type of lithium secondary battery, a separator may be provided between the positive electrode and the negative electrode. Polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of at least two layers thereof may be used as such a separator. Alternatively, a mixed multilayer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator may be used.
[0124] Lithium secondary batteries can be categorized as lithium-ion batteries, lithium-ion polymer batteries, and lithium polymer batteries based on the type of separator and electrolyte used. They can be categorized by shape, such as cylindrical, prismatic, coin, and pouch types. They can also be categorized by size, such as block and thin-film types. The structures and preparation methods of these batteries are well known in the art and will not be detailed here.
[0125] Hereinafter, preferred embodiments of the present invention and comparative examples will be described. However, the following embodiment is only a preferred embodiment of the present invention, and the present invention is not limited to the following embodiment.
[0126] Preparation method of positive electrode active material precursor for lithium secondary battery
[0127] Figures 1a to 1c SEM photographs of positive electrode active material precursors according to examples of the present invention and comparative examples are shown.
[0128] Figure 1a The SEM image of the positive electrode active material precursor prepared in Example 1 below is shown. Figure 1b The SEM image of the positive electrode active material precursor prepared in Example 2 below is shown. Figure 1c The SEM photograph of the positive electrode active material precursor prepared in the following Comparative Example 1 is shown. Figures 1a to 1c, it can be confirmed that the positive electrode active material precursors prepared in Examples 1 and 2 of the present invention tend to be thick and large.
[0129] Example 1
[0130] After adding 15% water to a 100L batch reactor relative to the total reactor volume, 5 parts by weight of sodium sulfate per 100 parts by weight of water were added to the reactor. Stirring was then performed at 400 rpm, and the internal temperature was set to 30 to 50°C. Nitrogen was introduced into the reactor to create an inert atmosphere. A 2.5M aqueous solution of metal sulfates, containing nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of 0.8:0.1:0.1, was then prepared along with 25% sodium hydroxide and 28% aqueous ammonia.
[0131] The flow rate of the metal sulfate aqueous solution was adjusted to 3 L / hour, the flow rate of the ammonia water was adjusted to 0.1 times the flow rate of the metal sulfate aqueous solution, and the amount of sodium hydroxide (NaOH) solution added was adjusted so that the hydrogen ion concentration (pH) in the reactor was approximately 11.0 to 12.0.
[0132] The reactants were then added to maintain a stirring speed of 500 rpm and an average residence time of 20 hours for the total solution. The reaction temperature was maintained at 40 to 70°C, and an inert atmosphere was maintained by adding nitrogen. After the reaction, the resulting solution was washed with water and subjected to solid-liquid separation using a filter press. Residual moisture was removed using high-pressure fresh air. The separated active material was dried in a fluidized bed dryer at 100 to 200°C.
[0133] The hydroxide particles obtained by the aforementioned method were mixed with lithium hydroxide at an equivalent ratio of 1.05 to the hydroxide, thereby preparing a positive electrode active material precursor.
[0134] Example 2
[0135] After adding 15% water to a 100L batch reactor relative to the total reactor volume, 10 parts by weight of sodium sulfate per 100 parts by weight of water was added to the reactor. Stirring was then performed at 400 rpm, and the internal temperature was set to 30 to 50°C. Nitrogen was introduced into the reactor to create an inert atmosphere. A 2.5M aqueous solution of metal sulfates, containing nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of 0.8:0.1:0.1, was then prepared along with 25% sodium hydroxide and 28% aqueous ammonia.
[0136] The flow rate of the metal sulfate aqueous solution was adjusted to 3 L / hour, the flow rate of the ammonia water was adjusted to 0.2 times the flow rate of the metal sulfate aqueous solution, and the amount of sodium hydroxide (NaOH) solution added was adjusted so that the hydrogen ion concentration (pH) in the reactor was approximately 11.5 to 12.5.
[0137] The reactants were then added to a stirring speed of 400 rpm, with an average residence time of 20 hours for the total solution. The reaction temperature was maintained at 40 to 70°C, and nitrogen was added to maintain an inert atmosphere. After the reaction, the resulting solution was washed with water and subjected to solid-liquid separation using a filter press. Residual moisture was removed using high-pressure fresh air. The separated active material was dried in a fluidized bed dryer at 100 to 200°C.
[0138] The hydroxide particles obtained by the aforementioned method were mixed with lithium hydroxide at an equivalent ratio of 1.05 to the hydroxide, thereby preparing a positive electrode active material precursor.
[0139] Comparative Example 1
[0140] After 15% of water was added to the 100 L batch reactor relative to the total volume of the reactor, no further sodium sulfate was added. The implementation method was the same as that of Example 1.
[0141] Evaluation Example - Precursor Characteristics
[0142] Table 1 below shows XRD characteristics of the precursors and single crystals according to Examples 1, 2 and Comparative Example 1.
[0143] For the XRD characteristics, a SMARTLAB instrument from Rigaku Corporation of Japan was used.
[0144]
Table 1
[0145]
[0146] Figure 2 XRD peak intensity values of Examples according to the present invention and Comparative Examples are shown.
[0147] from Figure 2 It can be confirmed that Examples 1 and 2 fall within the XRD peak intensity value range of the present invention, while Comparative Example 1 does not fall within the XRD peak intensity value range of the present invention.
[0148] Examples 3, 4 and Comparative Example 2 - Positive Electrode Active Materials
[0149] The positive electrode active material precursors formed in Examples 1, 2 and Comparative Example 1 were heated at a heating rate of 2.5° C. / min in an oxygen environment and then calcined at 780° C. for 9 hours to prepare a lithium composite metal oxide having a uniform single crystal structure.
[0150] Evaluation Example - Surface Analysis of Particles of Positive Electrode Active Materials for Lithium Batteries with Single Crystal Structure and Evaluation of Button Cells price
[0151] Table 2 below shows particle surface analysis based on the content of the complex ion former according to Example 3, Example 4, and Comparative Example 2, and button cell evaluation.
[0152] To evaluate the coin cell battery, a coin-type (CR2032) half-cell (button cell) was assembled in a moisture-controlled dry room. After battery assembly, the cells were immersed in electrolyte and aged at room temperature for 2 h to achieve electrochemical equilibrium.
[0153] For button cells, a TOSCAT-3100 charger and discharger was used for evaluation. First, for formation, a current density of 0.1C was applied in a voltage range of 2.5V-4.25V for one cycle of charge and discharge, and then a current density of 0.3C was applied in the same voltage range for charge and discharge. Table 2 below shows the capacity retention rate during evaluation at high temperature using the initial discharge capacity and coulombic efficiency (C efficiency) in the formation step and the high-temperature capacity retention rate.
[0154]
Table 2
[0155]
[0156]
[0157] Figures 3a to 3c SEM photographs of positive electrode active materials of lithium secondary batteries according to examples of the present invention and comparative examples are shown.
[0158] Figures 3a to 3c The positive electrode active materials of Example 3, Example 4 and Comparative Example 2 are shown respectively. Compared with Comparative Example 2, it can be confirmed that Examples 3 and 4 of the present invention are more uniform and exhibit a single crystal shape.
[0159] Figure 4a and Figure 4b Graphs showing capacity characteristics and lifespan characteristics of positive electrode active materials for lithium secondary batteries according to examples of the present invention and comparative examples.
[0160] according to Figure 4a and Figure 4b , compared with Comparative Example 2, it can be confirmed that the positive electrode active materials of Examples 3 and 4 have excellent capacity characteristics and life characteristics.
[0161] Evaluation Example - Characteristics of Sodium Sulfate as a Complex Ion Forming Agent
[0162] Figure 5 An SEM photograph of an active material precursor for a lithium secondary battery prepared by adding ammonium sulfate in a comparative example of the present invention is shown.
[0163] Figure 5 An SEM photograph of an active material precursor for a lithium secondary battery prepared by adding ammonium sulfate into a reactor is shown. Figure 1a and Figure 1b This is an SEM photo of the positive electrode active material precursor prepared using sodium sulfate under initial reaction conditions. Figure 5 This is an SEM photo of the positive electrode active material precursor prepared using sodium sulfate under initial reaction conditions.
[0164] from Figure 1a 、 Figure 1b and Figure 5 It can be confirmed that the precursor prepared by adding sodium sulfate (ie Figure 1a and Figure 1b The primary particles) are prepared by adding ammonium sulfate Figure 5 The precursor is thicker and larger. In addition, the crystals of the material using sodium sulfate are more uniform and present a single crystal shape, which confirms that sodium sulfate is more preferable as one of the initial reaction conditions than ammonium sulfate.
[0165] The preferred embodiments are described in detail above, but the scope of the present invention is not limited to the above embodiments. Various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention.
Claims
1. A positive electrode active material precursor, wherein: For XRD peaks, I 001 / I 100 The ratio is 0.5 to 6. 001 / I 101 The ratio is 0.6 to 3. 001 / I 102 The ratio is 2.5 to 8. 001 / I 110 The ratio is 1.5 to 11. 001 / I 111 The ratio is 2 to 14. 100 / I 001 The ratio is 0.1 to 3.1, I 100 / I 101 The ratio is 0.1 to 1.5, I 100 / I 102 The ratio is 1.0 to 7.
3. 100 / I 110 The ratio is 1.5 to 3.2, and I 100 / I 111 The ratio is at least any one of 2.5 to 5.3, For XRD peaks, I 001 Indicates the peak value that meets the range of 18.5±1.0°, I 100 Indicates the peak value that meets the range of 33.0±1.0°, I 101 Indicates the peak value that meets the range of 38.5±1.5°, I 102 Indicates the peak value that meets the range of 52.5±1.5°, I 110 Indicates the peak value that meets the range of 59±1.5°, I 111 Indicates a peak value that satisfies the range of 63±1.0°.
2. The positive electrode active material precursor according to claim 1, wherein The positive electrode active material precursor satisfies at least one of the following conditions: the half-width of the diffraction peak on the (001) plane is in the range of 0.1 to 3.0, the half-width of the diffraction peak on the (100) plane is in the range of 0.1 to 2.8, the half-width of the diffraction peak on the (101) plane is in the range of 0.36 to 1.0, the half-width of the diffraction peak on the (102) plane is in the range of 0.1 to 2.0, and the half-width of the diffraction peak on the (110) plane is in the range of 0.1 to 3.
0.
3. The positive electrode active material precursor according to claim 1, wherein The positive electrode active material precursor has a structure in which a transition metal layer and an oxygen layer are stacked at least one layer.
4. The positive electrode active material precursor according to claim 3, wherein The transition metal layer and the oxygen layer form an aggregate stacked by hydrogen bonding.
5. The positive electrode active material precursor according to claim 4, wherein The positive electrode active material precursor is composed of at least one primary particle. The c-axis crystal constant value of the primary particles is 300 nm to 700 nm.
6. A lithium secondary battery positive electrode active material, wherein: The positive electrode active material comprises <001> at least one positive electrode active material precursor having hydrogen bonds in the direction, The positive electrode active material is a single particle, and the single particle contains 500 to 2000 ppm of Li2CO3 in terms of weight %.
7. The positive electrode active material for a lithium secondary battery according to claim 6, wherein: The positive electrode active material comprises LiOH, The LiOH and the Li2CO3 satisfy the following formula 1, <Formula 1> 0.5≤[LiOH] / [Li2CO3]≤1.9 In Formula 1, [LiOH] represents the content of LiOH, and [Li2CO3] represents the content of Li2CO3.
8. The positive electrode active material for lithium secondary battery according to claim 6, wherein: In terms of weight %, LiOH contains 1000 to 4000 ppm.
9. The positive electrode active material for lithium secondary battery according to claim 6, wherein: The average particle size (D50) of the positive electrode active material is 2 to 20 μm.
10. The positive electrode active material for lithium secondary battery according to claim 6, wherein: The specific surface area of the positive electrode active material is 1 to 30 m 2 / g.
11. The positive electrode active material for lithium secondary battery according to claim 6, wherein: The positive electrode active material is a lithium nickel composite oxide represented by the following chemical formula 1: <Chemical Formula 1> Li x [Ni y Co z Mr w M v ]O2 In the above chemical formula 1, M is one or more selected from Ba, Ca, Zr, Ti, Mg, Ta, Nb and Mo, 0.9 <x<1.2,0.8<y<1,0<z<0.8,0<w<0.05,0≤v≤0.2。 12. A method for preparing a positive electrode active material, comprising: A step of adding an aqueous solution containing a sodium or potassium-based substance to form an initial reaction condition in the reactor; The step of adding an aqueous solution of a metal salt containing at least one of nickel, cobalt and manganese, a complex ion forming agent and a pH adjusting agent into the reactor to prepare a reaction solution; The step of filtering the reaction solution to prepare a metal composite hydroxide; The step of mixing the metal composite hydroxide and a lithium raw material to prepare a positive electrode active material precursor; as well as The positive electrode active material precursor is calcined. The aqueous solution including the sodium or potassium-based substance includes 5 to 10 parts by weight of the sodium or potassium-based substance relative to 100 parts by weight of water.
13. The method for preparing a positive electrode active material according to claim 12, wherein: The sodium or potassium-based substance includes at least any one of sodium sulfate, sodium hydrochloride, potassium hydrochloride, and potassium sulfate.
14. The method for preparing a positive electrode active material according to claim 12, wherein: In the step of adding an aqueous solution of a metal salt containing at least one of nickel, cobalt and manganese, a complex ion forming agent and a pH adjusting agent into the reactor, The ratio of the flow rate of the ammonia water to the flow rate of the aqueous metal salt solution is 0.06 to 0.
3.
15. The method for preparing a positive electrode active material according to claim 14, wherein: The flow rate of the aqueous metal salt solution is 2.5 to 3.5 L / hour.
16. The method for preparing a positive electrode active material according to claim 12, wherein: The calcination step is carried out at 750 to 1100°C.
17. The method for preparing a positive electrode active material according to claim 12, wherein: The calcination step is carried out for 5 to 30 hours.
18. The method for preparing a positive electrode active material according to claim 12, wherein: In the step of adding an aqueous solution of a metal salt containing at least one of nickel, cobalt and manganese, a complex ion former and a pH adjuster into the reactor, the pH in the reactor is adjusted to 10 to 12.